2019
DOI: 10.2147/copd.s224763
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overexpression Of hsa-miR-664a-3p Is Associated With Cigarette Smoke-Induced Chronic Obstructive Pulmonary Disease Via Targeting FHL1</p>

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is recognized as a chronic lung disease with incomplete reversible airflow limitation, but its pathophysiology was still not clear. This study aimed at investigating regulatory roles of special miRNA–mRNA axis in COPD development.MethodsDifferentially expressed miRNAs and downstream mRNAs were screened from the Gene Expression Omnibus (GEO) dataset by using the LIMMA package in R software. Weighted Gene Co-expression Network Analysis (WGCNA) was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Some miRNAs are upregulated directly by CSE, like miR-21, which is induced by hypoxia-inducible factor 1-alpha (HIF-1α) ( 114 , 164 ), or others, like miR-664a-3p (targets FHL1 ), which is raised in lung tissue and peripheral blood mononuclear cells (PBMCs) from COPD patients, and in Beas-2B cells exposed to CSE ( 165 ). Exosomes are also carriers for pathogenic miRNAs, as CSE-treated HBECs produce exosomes carrying miR-21, inducing myofibroblast differentiation and increasing α-SMA and collagen-I through HIF-1α.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…Some miRNAs are upregulated directly by CSE, like miR-21, which is induced by hypoxia-inducible factor 1-alpha (HIF-1α) ( 114 , 164 ), or others, like miR-664a-3p (targets FHL1 ), which is raised in lung tissue and peripheral blood mononuclear cells (PBMCs) from COPD patients, and in Beas-2B cells exposed to CSE ( 165 ). Exosomes are also carriers for pathogenic miRNAs, as CSE-treated HBECs produce exosomes carrying miR-21, inducing myofibroblast differentiation and increasing α-SMA and collagen-I through HIF-1α.…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…The authors could not show the possible role of miR-212-5p in CSE-treated conditions. There is evidence that peripheral blood mononuclear cells and lung tissues obtained from COPD patients exhibited a higher level of miR-664a-3p compared to smokers [57]. Additionally, overexpression of miR-664a-3p in BEAS-2B cells negatively regulated FHL1 mRNA and protein levels.…”
Section: Copdmentioning
confidence: 99%
“…Additionally, overexpression of miR-664a-3p in BEAS-2B cells negatively regulated FHL1 mRNA and protein levels. The authors suggested further work to elucidate the roles of miR-664a-3p and FHL1 in COPD [57].…”
Section: Copdmentioning
confidence: 99%
“…In COPD, miR-206 facilitated cell apoptosis in human pulmonary microvascular endothelial cells by the direct regulation of Notch3 and VEGFA; 26 miR-664a-3p overexpression was accountable for CSE-induced COPD through inhibiting FHL1. 27 Tang et al declared that miR-29b downregulation participated in the airway inflammation via upregulating BRD4. 28 In this chapter, miR-485-3p was discovered to have target relation with TLR4.…”
Section: Discussionmentioning
confidence: 99%